Development of a rat cell line containing stably integrated copies of a lambda/ lacI shuttle vector - Wyborski, Denise L.; Malkhosyan, Sergei; Moores, Jane; Perucho, Manuel; Short, Jay M. (Mutation Research, 1995)
A rat embryo cultured cell line was generated that carries stably integrated copies of a lambda/ lacI shuttle vector, containing the lacI gene as a mutational target. After the desired treatment of the cells, this vector can be rapidly and efficiently recovered fron the cell DNA by in vitro packaging and then screnned for mutations in the lacI gene, using bacterial detection systems. The vector is identical to that integrated into the Big Blue transgenic mouse, which was developed for in vivo mutation analysis. Characterization of the cell line by fluorescence in situ hybridization showed that the phage DNA is integrated at two distinct sites on separate chromosomes at approximately 50–70 copies per cell and the cell line is polyploid. The rescue efficiency is approximately 100 000 pfu/μg of genomic DNA. To examine the ability of the cell line to detect mutations in the lacI gene, the cells were treated with 100 μg/ml of the direct-acting alkylating agent N-methyl- N-nitrosourea (MNU) for 30 min at 37°C and grown to confluence. The shuttle vector was rescued from untreated and mutagen treated cells, and spontaneous and induced mutant frequencies were determined to be 4.0 × 10 −5 and 92.7 × 10 −5, respectively. The cell line can be used to detect mutations in the lacI gene, followed by recovery of mutants for sequence analysis. The cell line may be valuable for short-term in vitro mutagenesis studies, oncogene and tumor suppressor studies, and DNA repair studies.